A Novel Microfluidic Chip for Fast, Sensitive Quantification of Plasma Extracellular Vesicles as Biomarkers in Patients With Osteosarcoma - Xu, Yi-Qi; Bao, Qi-Yuan; Yu, Sai-Xi; Liu, Qi; Xie, Yan; Li, Xin; Liu, Yan-Jun; Shen, Yu-Hui (Frontiers in Oncology, 2021)
Plasma circulating extracellular vesicle (EV) has emerged as a promising biomarker for diagnosis and prognosis of various epithelial tumors. However, fast and efficient capture of EVs with microfluidic chip in sarcoma remains to be established. Herein, we reported a ZnO-nanorods integrated (ZNI) microfluidic chip, where EV capture antibody was uniformly grafted to the surface of the ZnO-nanorods of the chip to enhance the plasma turbulence formation and the capture efficiency at the micro-scale. Based on osteosarcoma (OS) cell line, we demonstrated that a combination of CD81 and CD63 antibody on ZNI chip yielded the greatest amount of total EVs, with an extra sensitive limit of detection (LOD) of ~104 particles mL-1. Furthermore, the addition of fluorescent labeling of Vimentin (VIM), a previously reported sarcoma cell surface biomarker, could enabled the dual visualization of total plasma EVs and VIM-positive EVs from OS patients’ plasma. Based on our ZNI chip, we found that the amount of plasma total EVs was significantly different between OS and healthy donors (OS:1562.057 a.u., healthy donor: 638.565 a.u., p=0.003), but not between metastatic and nonmetastatic OS (p>0.100). Interestingly, patients with metastatic disease had a significantly greater amount of VIM-positive EVs (1410.790 versus 231.059, p=0.003) and increased VIM-positive/ total EVs ratio (0.943 versus 0.211, p=0.045) in comparison with the nonmetastatic counterpart. Therefore, our ZNI microfluidic chip has great potential for the fast quantification of plasma EVs, and the microfluidic-based quantification of total and VIM-positive EVs might serve as a promising biomarker for the diagnosis and surveillance in OS patients.